Neuropeptide Bursicon Influences Reproductive Physiology in Tribolium Castaneum - Li, Jingjing; Zhu, Zidan; Bi, Jingxiu; Feng, Qili; Beerntsen, Brenda T.; Song, Qisheng (Frontiers in Physiology, 2021)
Bursicon is a cystine knot family neuropeptide, composed of bursicon (burs) and partner of bursicon (pburs) subunits. It can form heterodimers or homodimers to execute different biological functions. The heterodimers regulate cuticle sclerotization and wing maturation while homodimers mediate innate immunity and midgut stem cell proliferation. A recent study showed that bursicon could induce the expression of vitellogenin (Vg) in the black tiger shrimp Penaeus monodon; however, the underlying mechanism remains unknown. In the present study, we investigated the role of bursicon in the reproductive physiology of the red flour beetle, Tribolium castaneum. Knock-down of burs, pburs or Tcrk in 2-day pupae significantly down-regulated the expression levels of Vg1, Vg2 and Vg receptor (VgR) genes in the females 3- and 5-day post adult emergence, leading to abnormal oocytes with limited Vg content. Silencing of burs repressed the number of eggs laid and completely inhibited egg hatch, while silencing of pburs dramatically decreased the number of eggs laid, hatch rate and offspring larval size, and these RNAi effects persisted to the next generation. Furthermore, knockdown of burs or pburs down-regulated the expression of the insulin/insulin-like (IIS)/target of rapamycin (TOR) signaling genes encoding insulin receptor (InR), protein kinase B (Akt), TOR and ribosomal protein S6 kinase (S6K). Most importantly, injection of recombinant pburs protein was able to up-regulate expression of Vg, VgR, InR, Akt, TOR, S6K, JHAMT, Met and Tai in the normal females and rescue the expression of Vg and VgR in the pburs RNAi females, but failed to rescue Vg and VgR in the Tcrk knockdown females. We infer that bursicon homodimers influence Vg expression via receptor Tcrk, possibly by mediating the expression of the JH and IIS/TOR pathway genes, thereby regulating reproduction in T. castaneum.